Assessing Vocal Chanting as an Online Psychosocial Intervention - Simpson, Felicity Maria; Perry, Gemma; Thompson, William Forde (Frontiers in Psychology, 2021)
The ancient practice of chanting typically takes place within a community as a part of a live ceremony or ritual. Research suggests that chanting leads to improved mood, reduced stress, and increased wellbeing. During the global pandemic, many chanting practices were moved online in order to adhere to social distancing recommendations. However, it is unclear whether the benefits of live chanting occur when practiced in an online format. The present study assessed the effects of a 10-minute online chanting session on stress, mood, and connectedness, carried out either in a group or individually. The study employed a 2 (chanting vs control) x 2 (group vs individual) between-subjects design. Participants (N = 117) were pseudo-randomly allocated across the four conditions. Before and after participation, individuals completed the Spielberg’s State Trait Anxiety Inventory, the Positive and Negative Affect Schedule, Social Connectedness Scale and Aron’s Inclusion of Self in Other Scale. Online chanting led to a significant reduction in stress and an increase in positive affect when compared to the online control task. Participants who took part in group chanting also felt more connected to members of their chanting group than participants in the control group. However, feelings of general connectedness to all people remained similar across conditions. The investigation provides evidence that online chanting may be a useful psychosocial intervention, whether practiced individually or in a group.